The Effect of Inclusive Leadership on Organizational Agility: An analytical study in the General Company of Battery Industry - Abbas Abdel Khalil*, Heba; Mahdi Saleh, Khaled (Journal of Economics and Administrative Sciences, 2024)
Purpose: Explaining the impact of comprehensive leadership in achieving organizational agility that contributes to achieving the desired goals and retaining competent cadres. Theoretical framework: Achieving the primary goal, which is by defining the effect of inclusive leadership with its dimensions on organizational agility. The research investigated the extent to which comprehensive leadership contributes to enhancing organizational agility through employees’ ownership of the two concepts. Design/methodology/approach: The descriptive-analytical method was adopted, and the data were analyzed to reach the results using SPSS V.26 software. The company registration department, a subsidiary of the General Company for Battery Industries, was chosen to represent the study population. Data was collected from 111 employees, including managers and employees, using a a questionnaire. It was analyzed using statistical methods such as arithmetic mean, standard deviation, and simple linear regression. Findings: The higher level of managers adopting inclusive leadership, and organizational flexibility. Research, practical & social implications: Promoting a culture within the organization that encourages proactiveness and interest in innovation. This can be achieved by encouraging the manager and employees to share new ideas and suggestions. Originality/value: Describing contemporary administrative concepts that play a major role in improving the level of public services provided to citizens.